(untitled) (Minerva. Revista de Filología Clásica, 2019)
This article deals with the presentation and partial edition of the MS 165 of the Fernán Núñez Collection (University of California, at Berkeley), which contains an unknown bilingual Latin grammar written by Blas López de Miranda in both Castilian and Latin. This prosimetrum, which was probably composed to be published, is preserved in a fragmentary form in a MS that also contains an unknown copy of Góngora’ s Las firmezas de Isabela. López de Miranda’s work is paramount as an example of the writing of basic grammatical and metrical Latin treatises in the 17th century and its edition will serve to improve our knowledge of the Iberian Peninsula Latin grammatical tradition.